2000
DOI: 10.1023/a:1007550801444
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Platelet-activating factor (PAF, 1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine) and its receptor are known to play important roles in modulating neuronal plasticity and inflammatory responses, particularly during neuronal injury. PAF receptors are widespread in different brain regions and are present on the cell surface as well as in intracellular membrane compartments. Astrocytes are immune active cells and are responsive to cytokines, which stimulate signaling cascades leading to transcriptional activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In primary and immortalized astrocytes of rat origin, induction of sPLA2-IIA can be mediated independently by TNFα and IL-1β, without the involvement of IFNγ [21,22,28,36]. Since BV-2 cells are of murine origin, it is not surprising that these cells lack the ability to induce sPLA2-IIA upon exposure to cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In primary and immortalized astrocytes of rat origin, induction of sPLA2-IIA can be mediated independently by TNFα and IL-1β, without the involvement of IFNγ [21,22,28,36]. Since BV-2 cells are of murine origin, it is not surprising that these cells lack the ability to induce sPLA2-IIA upon exposure to cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that when stimulated by cytokines such as TNF α and IL-1β, DITNC astrocytes showed increased mRNA expression of sPLA 2 -IIA (Li et al, 1999; Wang and Sun, 2000; Jensen et al, 2009). In this study, we first determined whether stimulation of DITNC astrocytes with TNF α and IL-1β induced sPLA 2 -IIA secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Increase in sPLA 2 -IIA mRNA was also observed in the rat brain after focal cerebral ischemia (Lin et al, 2004). In studies with astrocytes, pro-inflammation cytokines were shown to increase sPLA 2 -IIA mRNA expression through activation of the NF-jB transcription pathway (Li et al, 1999; Wang and Sun, 2000; Jensen et al, 2009). sPLA 2 -IIA from astrocytes was linked to the production of reactive oxygen species and apoptosis through activation of the superoxide producing enzyme NADPH oxidase in neurons (Yagami et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation